The Application of Practice-Based Simulation to New Nurses on Clinical Skills and Self-Confidence - Yusriani Saleh Baso; Fitri Arofiati (Universitas Aisyah Pringsewu, 2022)
Background: To enhance the self-confidence and clinical skills of new nurses, it is necessary to have a learning process (education and training) utilizing the simulation learning method or Practice-Based Simulation.Research Purposes: This study aims to analyze the effect of Practice-Based Simulation on the clinical skills and self-confidence of new nurses at the Islamic General Hospital of Harapan Anda, Tegal.Research Methods: This study used the Quasy-Experiment method with a pretest-posttest approach using a control group design. A total of 40 respondents from both the intervention and control groups were sampled using a simple random sampling procedure. The study was conducted for four weeks. The instruments used were questionnaires and SPO. Data analysis was performed using Paired t-Test and Independent Samples t-Test. Results: The study’s findings revealed that the difference in clinical skills of ECG insertion in the intervention group was 9.65 points and 6.90 points in the control group. Meanwhile, the difference in clinical skill of infusion in the intervention group was 10.30 points and 7.20 points in the control group. Furthermore, the difference in the increase in self-confidence in the intervention group was 34.90 points and 23.35 points in the control group. Statistical tests using Independent Samples t-Test for clinical skills found that p= 0.00, which was less than 0.05 while for self-confidence,p = 0.00, which was less than 0.05.Conclusion: It was concluded that Practice-Based Simulation affects clinical skills and self-confidence in new nurses at the Islamic General Hospital of Harapan Anda, Tegal. Abstrak: Latar Belakang: Untuk meningkatkan kepercayaan diri dan keterampilan klinis perawat baru perlu adanya proses pembelajaran (pendidikan dan latihan) dengan menggunakan metode pembelajaran simulasi atau Practice Based Simulation. Tujuan Penelitian: Penelitian ini bertujuan untuk menganalisis pengaruh practice based simulation terhadap keterampilan klinis dan kepercayaan diri pada perawat baru di RSU Islam Harapan Anda Tegal. Metode Penelitian: Menggunakan metode Quasy–Experiment dengan pendekatan pretest-posttest with kontrol group design. Pengambilan sampel dengan teknik simple random sampling dengan jumlah 40 responden baik kelompok intervensi maupun kelompok kontrol. Penelitian dilakukan selama empat minggu, Instrumen yang digunakan adalah kuesioner dan SPO. Analisis data menggunakan uji Paired T-Test dan Independent Samples T-Test. Hasil: Hasil penelitian selisih peningkatan keterampilan klinis pemasangan EKG pada kelompok intervensi sebanyak 9,65 poin dan pada kelompok kontrol 6,90 poin , dan untuk keterampilan klinis pasang infus pada kelompok intervensi sebanyak 10,30 poin dan kelompok kontrol sebanyak 7,20 poin, sedangkan untuk selisih peningkatan self confidence pada kelompok intervensi sebanyak 34,90 poin dan kelompok kontrol sebanyak 23,35 poin. Uji Statistik menggunakan Independent Samples T-Test untuk keterampilan klinis didapatkan bahwa P=0.00 kurang dari 0.05 sedangkan untuk kepercayaan diri P=0.00 kurang dari 0.05. Kesimpulan: Disimpulkan bahwa practice based simulation mempengaruhi keterampilan klinis dan kepercayaan diri pada perawat baru di RSU Islam Harapan Anda Tegal.